Respuesta :

ANSWER

By simplifying the left hand side using the Pythagorean Identity.

EXPLANATION

The given identity is

[tex] \csc^{2} (x) - \cot^{2} (x) = 1[/tex]

Take the left hand side and simplify to get the right hand side.

[tex] \csc^{2} (x) - \cot^{2} (x) = \frac{1}{\sin^{2} (x)} - \frac{ \cos^{2} (x)}{\sin^{2} (x)} [/tex]

Collect LCM for the denominators.

[tex]\csc^{2} (x) - \cot^{2} (x) = \frac{1 - \cos^{2} (x)}{\sin^{2} (x)} [/tex]

Recall the Pythagorean Identity.

[tex] \cos^{2} (x) + \sin^{2} (x) = 1[/tex]

This implies that:

[tex]1 - \cos^{2} (x) = \sin^{2} (x)[/tex]

We substitute this to get,

[tex]\csc^{2} (x) - \cot^{2} (x) = \frac{\sin^{2} (x)}{\sin^{2} (x)} [/tex]

[tex]\csc^{2} (x) - \cot^{2} (x) = 1[/tex]